XML technology assisted research paper abstract writing - Castel, Víctor M. (2006)

(untitled)
iven its briefness, inherent complexity and massive and critical use in scientific discourse, the research paper abstract (RP A) is a text type particularly interesting for both linguistic modelling (writing and reading) and automatic processing (generation and parsing). Even though the current literature on these fields is large and promising, there are still various gaps to fill, especially in the domain of the interplay between linguistic modelling and the development of applications for the solution of communication problems. Our purpose here is to present the RedACTe Project's approach to the design of software oriented to rhetorical and linguistic assistance in RP A writing